2020
DOI: 10.1007/s00026-019-00478-z
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Energy Bound for Distinct Perpendicular Bisectors

Abstract: Let P be a set of n points in the Euclidean plane. We prove that, for any ε > 0, either a single line or circle contains n/2 points of P, or the number of distinct perpendicular bisectors determined by pairs of points in P is Ω(n 52/35−ε ), where the constant implied by the Ω notation depends on ε. This is progress toward a conjecture of Lund, Sheffer, and de Zeeuw, that either a single line or circle contains n/2 points of P, or the number of distinct perpendicular bisectors is Ω(n 2 ).The proof relies boundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…If no circle or line contains more than M points of A, then Q M = Q, and we recover Theorem 2. Theorem 3 follows from the arguments in [11] by using Theorem 17 in place of [11,Lemma 11].…”
Section: Proof Of Theorem 2 and Sketch Of Proof Of Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…If no circle or line contains more than M points of A, then Q M = Q, and we recover Theorem 2. Theorem 3 follows from the arguments in [11] by using Theorem 17 in place of [11,Lemma 11].…”
Section: Proof Of Theorem 2 and Sketch Of Proof Of Theoremmentioning
confidence: 99%
“…The conjecture of Lund, Sheffer, and de Zeeuw on this question is that, for a set A of N points in R 2 , either N/2 points are contained in a single line or circle, or A determines Ω(N 2 ) distinct perpendicular bisectors. Lund, Sheffer, and de Zeeuw showed that a set of N points, no more than M of which are incident to any line or circle, determines Ω ε (min(M −2/5 N 8/5−ε , M −1 N 2 )) distinct perpendicular bisectors, for any ε > 0, with the implied constant depending on ε. Lund [11] showed that a set of N points in the plane, no more than N/2 of which are incident to any line or circle, determines Ω ε (N 52/35−ε ) distinct perpendicular bisectors, for any ε > 0, with the implied constant depending on ε. A slight generalization of Theorem 2, combined with the arguments of [11], gives the following improvement to Lund's bound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation